The Implementation of Military Leadership Training Programme; Reserve Officer Training Unit (ROTU) In Shaping Islamic Moral Among Cadets: A Study In Universiti Sains Islam Malaysia (USIM) - Nurus Saadah, Md Yusof; Qistina Balkis, Mohd Yusof; Rashidi, Abbas (Global Business and Social Entrepreneurship Resources, 2017)
ROTU training program is one of the curriculum courses in USIM, that determine to transform holistic graduates, where all the students must dominate all the soft skills such as leadership, teamwork, communication and continuous learning. Therefore, this study wants to identify the implementation of military leadership training program (ROTU) in shaping Islamic moral among its cadets. The objective of this study is to find out the problems associated with moral among cadets; the factors contribute towards it, and the ways to overcome it. A set of questionnaire were distributed to 60 respondents, which are among the third year students who participate in ROTU UKM. Then, the data collected were analysed by using Statistical Package for Social Science (SPSS) 20.0. As for conclusion, the findings indicated that the military leadership training program give a positive effect and lot of benefits toward cadets. For the purpose of further study in the future, researchers suggested that this study will use different methods and respondents.